P697Evaluation of tp-te interval and tp-te/qt ratio in patients with coronary slow flow tp-te/qt ratio and coronary slow flow. (15th July 2014) - Karaagac, K; Demir, M; Yontar, O C; Tenekecioglu, E; Vatansever, F; Arican Ozluk, O; Tutuncu, A; Arslan, B; Yilmaz, M
Abstract: Aims: Coronary slow flow (CSF) phenomenon is described by angiographically normal coronary arteries with delayed opacification of the distal vasculature. Studies have suggested that the interval from the peak to the end of the electrocardiographic T wave (Tp-Te) may correspond to the transmural dispersion of repolarization and that increased Tp-Te interval and Tp-Te/QT ratio are associated with malignant ventricular arrhythmias. The aim of this study was to evaluate ventricular repolarization by using Tp-Te interval and Tp-Te/QT ratio in patients with CSF. Materials and Method: This study included 50 CSF patients (40 male, mean age 48, 6±12, 5 years) and 40 control person (23 male, mean age 47, 8±12, 5 years). Tp-Te interval and Tp-Te/QT ratio were measured from the 12-lead electrocardiogram. These parameters were compared between groups Results: Baseline characteristics of the study groups were comparable. In electrocardiographic parameters analysis, QT and corrected QT were similar in CSF patients compared to the controls (357±35, 2 vs 362±38, 0 milliseconds and 419±25, 8 vs 430±44, 2 milliseconds, all p value >0, 05). Tp-Te interval, Tp-Te/QT and Tp-Te/QTc ratio were significantly higher in CSF patients (85±13, 7 vs 74±9, 9 milliseconds and 0, 24±0, 03 vs 0, 20±0, 02 and 0, 20±0, 03 vs 0, 17±0, 02 all P value <0, 001). Conclusion: Our study revealed that QTd, Tp-Te interval and Tp-Te/QT ratio are prolonged in patients with CSF. Table 1. Comparison of data in coronary slow flow patients and controls CSF group ( N=50) Control (n=40) p value Age (year) 48, 6±12, 5 47, 8±12, 5 NS Hypertension (%) 10 (20%) 26 ( 65%) NS Diabetes Mellitus (%) 3 (6%) 3 (7, 5%) NS Dyslipidemia (%) 19 (38%) 6 (15%) 0, 029 HDL-Cholesterol (mg/dL) 41±10, 4 51±14.1 0, 001 Mean frame count 23±5, 04 19±1, 7 <0, 001 LAD 20± 5, 4 17±1, 5 <0, 001 Cx 24±7, 8 20±2, 4 =0, 006 RCA 26±8, 7 19±1, 7 <0, 001 Tp-Te/QT ratio 0, 24±0, 03 0, 20±0, 02 <0, 001 Tp-Te/QTc ratio 0, 20±0, 03 0, 17±0, 02 <0, 001 LVEF (%) 60±3, 5 60±2, 4 NS